Failed Leadership - Kasianiuk, Krzysztof; Kasianiuk, Krzysztof; Zylicz, Piotr Olaf; Szklarski, Bohdan (Peter Lang, 2021)
Manifestations and causes of failed leadership have attracted little systematic scientific reflection. This collection of articles brings readers$1 (Battention to (3z(Bfailed leadership(3y (Baspects encompassing business, political, social, philosophical, psychological and historical perspectives presented. An international group of authors, ranging from academicians to business practitioners. The reader will find both advanced theoretical analyses as well as descriptions of real-life cases of failed leadership across time and different geographies. The publication revolves around critical questions, including: (3z(BIs failure a flip side of success?(3y(B, (3z(BHow to measure failure?(3y(B, (3z(BHow much does it depend on historical, cultural or situational contexts?(3y(B, or (3z(BIs failure recoverable?(3ys